ROBBINS & KUMAR BASIC PATHOLOGY - Kumar, Vinay; Abbas, Abul K.; Aster, Jon C.; Deyrup, Andrea T.; Das, Abhijit (Elsevier, 2023)
Readable, well-illustrated, and concise, Robbins and Kumar's Basic Pathology, 11th Edition, offers today's busy students a rich understanding of all essential pathology concepts from trusted names in the field. This updated edition thoroughly covers key pathologic processes and the time-honored tools of gross and microscopic analysis, while also retaining a strong emphasis on clinicopathologic correlations and the impact of molecular pathology on the practice of medicine. Outstanding artwork and schematic drawings, as well as a robust eBook experience with extensive additional features, make complex concepts easier to learn and retain.